Towards global mapping of dynamic surface water extents using Sentinel-1 SAR data - Jungkyo Jung; Heresh Fattahi; Seongsu Jeong; Matthew G. Bonnema; John W. Jones; David Bekaert; Steven K. Chan; Alexander L. Handwerger (Remote Sensing of Environment, 2026)

Young adulthood adiposity in relation to all-cause and cause-specific mortality: a prospective study of 0.5 million Chinese adults - Lei Fan; Andri Iona; Shixian Feng; Gang Zhou; Huarong Sun; Pang Yao; Canqing Yu; Yiping Chen; Dianjianyi Sun; Pei Pei; Ling Yang; Mingshu Yan; et al. (Science Bulletin, 2026)

Seeing the forest for the trees: white spruce (Picea glauca) tree bark as a biogeochemical indicator of a lithium occurrence in southwestern New Brunswick, Canada - Alexandre Voinot; A.M. Mloszewska; Steven Rossiter; Lyndsay Moore; Sabrina Chan; Margaret Linttell; Steve Day (Science of The Total Environment, 2026)

Efficacy of Inhalable Endolysin Cpl-1 Formulations in Combination with Gentamicin or Endolysin Pal in a Murine Lung Infection Model - Yuncheng Wang; Maxwell T. Stevens; Trixie Wang; Adit B. Alreja; Daniel C. Nelson; Warwick J. Britton; Hak-Kim Chan (Pharmaceutical Research, 2026)
Purpose Inhalable liquid formulation of endolysins represents a promising alternative to conventional antibiotics. Dry powder formulations offer improved stability for endolysin pulmonary delivery. This study aimed to evaluate the efficacy of an inhalable dry powder or liquid formulation of endolysin Cpl-1 alone and to compare it with liquid combinations of Cpl-1 with either gentamicin or endolysin Pal in a murine model of S. pneumoniae lung infection. Methods A dry powder formulation of Cpl-1 was produced via spray drying, while liquid formulations were prepared by dissolving Cpl-1, or in combination with gentamicin or endolysin Pal in liquid. The droplet size distribution of aerosolized formulations was also characterized. Mice were intratracheally infected with S. pneumoniae and treated with either powder or liquid formulations. The bacterial load in respiratory system was assessed 26 h post-infection. The stability and activity of Cpl-1 in BALF were also evaluated ex vivo . Results A single dose of Cpl-1 powder formulation or Cpl-1 liquid formulation (40 µg/mouse) reduced pulmonary bacterial load by approximately 1 log 10 . Importantly, the combination of Cpl-1 and Pal in liquid form resulted in a synergistic 2.0 log 10 reduction, significantly greater than either endolysin alone, while combining Cpl-1 with gentamicin did not enhance antibacterial activity. Ex vivo assays confirmed that Cpl-1 retained full enzymatic activity after incubation in BALF. Conclusion This proof-of-principle study demonstrated that inhalable endolysin liquid and powder formulations could potentially be used to treat bacterial lung infections. Moreover, the combination of multiple endolysins could increase antimicrobial activity over endolysin monotherapy.

Condition of coral communities in Victoria Harbour, Hong Kong as determined by mapping seascape metrics - Jeffery Tzu Hao Chung; Steven Hong Tai Tsang; Nicci Ng; Walter Dellisanti; Qin Xian; Jiajun Wu; James Kar Hei Fang; Jian-Wen Qiu; Kenneth Mei Yee Leung; Lai Leo Chan (Marine Pollution Bulletin, 2025)

Population genomic investigation of the Oregon Slender Salamander (Batrachoseps wrighti) reveals suburban populations are remnants, not recent introductions - Clare Yang; Laura Guderyahn; Charlotte Corkran; Steven Wagner; Lauren M. Chan (Conservation Genetics, 2025)

Development of an Anatomy-Mimicking, Wave Transport-Preserving Mock Circulation Loop for Evaluating Pulsatile Hemodynamics as Supported by Cardiovascular Assist Devices - Pong-Jeu Lu; Ming-Yao Chan; Steven Tsui; Tzung-Tza Shen; Jui-Chih Chang (Cardiovascular Engineering and Technology, 2025)
Objective Assessing circulatory hemodynamics in-vitro is crucial for cardiovascular device design before in-vivo testing. Current mock circulation loops (MCLs) rely on simplified, lumped-parameter hydraulic representations of human circulation. There is a need for a more sophisticated MCL that can accurately represent the human circulatory physiology and allow for critical assessment of device-supported hemodynamics. Methods An anatomy-mimicking MCL design guided by one-dimensional flow models has been developed, using tree-like arterial casts to create a complex system. The MCL comprises cardiac simulators, systemic circulatory subsystems consisting of 46 connected arterial casts, and lumped venous and pulmonary components. A parameter tuning process was also developed to ensure that the simulated MCL baselines are consistent with targeted healthy or heart failure scenarios. Results Blood pressure and flow waveforms in the thoracic aorta, upper and lower limb arteries and abdominal organs (kidney, liver, spleen, etc.) were reproduced and validated against published data. Complex afferent and efferent flows in cerebral circulation and phasic coronary flow subjected to myocardial compression effect were replicated with precision. Pulse wave behavior was authentically generated and compared favorably to the published in-vivo and in-silico results. Conclusion This wave transport-preserving MCL is able to simulate pulsatile human circulatory hemodynamics with sufficient detail and accuracy. Complex cardiovascular device-intervened hemodynamics in large arteries and end organs can be systematically assessed using this new MCL, potentially contributing to a rapid and accurate in-vitro simulation to help advance device design and functional optimization.

The impact of functional additives on biodegradable plastic biodegradation in natural terrestrial and composting environments - Clement Matthew Chan; Serena Yim; Paul Lant; Steven Pratt; Bronwyn Laycock (Critical Reviews in Environmental Science and Technology, 2025)

Habitat variations of sediment microbial community structure and functions and the influential environmental factors in a Ramsar protected wetland in South China - Kit-Ling Lam; Nora Fung-Yee Tam; Steven Jing-Liang Xu; Wing-Yin Mo; Yuet-Tung Tse; Kaze King-Yip Lai; Ping-Lung Chan; Fred Wang-Fat Lee (Marine Pollution Bulletin, 2024)

Lifetimes and mechanisms of biodegradation of polyhydroxyalkanoate (PHA) in estuarine and marine field environments - Tracey Read; Céline Chaléat; Bronwyn Laycock; Steven Pratt; Paul Lant; Clement Matthew Chan (Marine Pollution Bulletin, 2024)

Corrigendum to ‘Personal exposure monitoring of fine and coarse particulate matter using exposure assessment models for elderly residents in Hong Kong’ [Chemosphere 357 (June 2024) 141975] - Ka Hei Lui; Tianhang Zhang; Chung Ling Man; Chi Shing Chan; Steven Sai Hang Ho; Linli Qu; Helen Hoi Ling Kwok; Timothy Chi Yui Kwok; Kin Fai Ho (Chemosphere, 2024)

Personal exposure monitoring of fine and coarse particulate matter using exposure assessment models for elderly residents in Hong Kong - Ka Hei Lui; Tianhang Zhang; Chung Ling Man; Chi Shing Chan; Steven Sai Hang Ho; Linli Qu; Helen Hoi Ling Kwok; Timothy Chi Yui Kwok; Kin Fai Ho (Chemosphere, 2024)

The effect of additives on the biodegradation of polyhydroxyalkanoate (PHA) in marine field trials - Tracey Read; Clement Matthew Chan; Céline Chaléat; Bronwyn Laycock; Steven Pratt; Paul Lant (Science of The Total Environment, 2024)

Electron-phonon coupling from GW perturbation theory: Practical workflow combining BerkeleyGW, ABINIT, and EPW - Zhenglu Li; Gabriel Antonius; Yang-Hao Chan; Steven G. Louie (Computer Physics Communications, 2024)

Polyhydroxyalkanoate production in a biofilm by mixed culture phototrophic bacteria - Tim Hülsen; Daniel Venturato; Clement Chan; Luigi Vandi; Bronwyn Laycock; Steven Pratt; Samuel Stegman; Mark van Loosdrecht; Damien J. Batstone (Journal of Cleaner Production, 2024)

Characterising personal, household, and community PM2.5 exposure in one urban and two rural communities in China - Ka Hung Chan; Xi Xia; Cong Liu; Haidong Kan; Aiden Doherty; Steve Hung Lam Yim; Neil Wright; Christiana Kartsonaki; Xiaoming Yang; Rebecca Stevens; Xiaoyu Chang; Dianjianyi Sun; et al. (Science of The Total Environment, 2023)

Effects of driving conditions on aerosol formation from photooxidation of gasoline vehicles exhaust in Hong Kong - Hon Yin Poon; Ka Hei Lui; Yik-Sze Lau; Bruce Organ; Man Nin Chan; Hai Guo; Steven Sai Hang Ho; K.F. Ho (Atmospheric Environment, 2023)

Using social network analysis to track the evolution of Pacific food system research collaborations over time - Rachel S. Friedman; Ellis Mackenzie; Asenati L. Chan-Tung; Matthew G. Allen; Steven Crimp (Regional Environmental Change, 2023)
Climate change undermines the foundations of food and nutrition security, making it crucial to understand and improve the current research collaborations striving to fill knowledge gaps about the impacts on food systems. This study focuses on the network of research actors working on food systems and climate change in Pacific Island Countries and Territories (PICTs), a region particularly vulnerable to climate change, and actively integrating knowledge about climate impacts to inform adaptation planning. Specifically, this study looks at co-publication as a form of research collaboration and co-production, using network analysis to understand who are the prominent organizational actors driving knowledge development in the region. Overall, we found a distinct core of these organizations engaged in the research space, dominated in number by academic institutions largely based in Australia, the USA, and New Zealand, but knit together through the interactions of the regional government agencies of the Pacific Islands. Over time, the network of research collaboration on climate change and food systems in the region has grown and diversified. While regional Pacific institutions have remained central actors throughout, national and subnational actors are still in the minority, raising questions about efforts to decolonize research in the region. Furthermore, greater interaction between peripheral actors and the core (especially Pacific actors) could help integrate new research into Pacific knowledge bases and decision-making. Ultimately, when facing the novel conditions that climate change brings, combining the infusion of new knowledge and innovation with local expertise and ownership is critical.

Synthesis and characterisation of poly(3-hydroxybutyrate-co-3-hydroxyvalerate) (PHBV) multi-block copolymers comprising blocks of differing 3-hydroxyvalerate contents - Jingjing Mai; Christopher J. Garvey; Clement Matthew Chan; Steven Pratt; Bronwyn Laycock (Chemical Engineering Journal, 2023)

Characterization of chemical components of fresh and aged aerosol from vehicle exhaust emissions in Hong Kong - Ka Hei Lui; Yik-Sze Lau; Hon Yin Poon; Bruce Organ; Man-Nin Chan; Hai Guo; Steven Sai Hang Ho; K.F. Ho (Chemosphere, 2023)

Intra- and inter-habitat variation in sediment heavy metals, antibiotics and ecological risks in Mai Po RAMSAR, China - Kit-Ling Lam; Nora Fung-Yee Tam; Steven Jing-Liang Xu; Wing-Yin Mo; Ping-Lung Chan; Fred Wang-Fat Lee (Marine Pollution Bulletin, 2023)

Correction to: Evaluation of Alpine-Mediterranean precipitation events in convection-permitting regional climate models using a set of tracking algorithms - Sebastian K. Müller; Cécile Caillaud; Steven Chan; Hylke de Vries; Sophie Bastin; Ségolène Berthou; Erwan Brisson; Marie-Estelle Demory; Hendrik Feldmann; Klaus Goergen; Stergios Kartsios; Petter Lind; et al. (Climate Dynamics, 2023)

Evaluation of Alpine-Mediterranean precipitation events in convection-permitting regional climate models using a set of tracking algorithms - Sebastian K. Müller; Cécile Caillaud; Steven Chan; Hylke de Vries; Sophie Bastin; Ségolène Berthou; Erwan Brisson; Marie-Estelle Demory; Hendrik Feldmann; Klaus Goergen; Stergios Kartsios; Petter Lind; et al. (Climate Dynamics, 2023)

Attribution of the heavy rainfall events leading to severe flooding in Western Europe during July 2021 - Jordis S. Tradowsky; Sjoukje Y. Philip; Frank Kreienkamp; Sarah F. Kew; Philip Lorenz; Julie Arrighi; Thomas Bettmann; Steven Caluwaerts; Steven C. Chan; Lesley De Cruz; Hylke de Vries; Norbert Demuth; et al. (Climatic Change, 2023)
In July 2021 extreme rainfall across Western Europe caused severe flooding and substantial impacts, including over 200 fatalities and extensive infrastructure damage within Germany and the Benelux countries. After the event, a hydrological assessment and a probabilistic event attribution analysis of rainfall data were initiated and complemented by discussing the vulnerability and exposure context. The global mean surface temperature (GMST) served as a covariate in a generalised extreme value distribution fitted to observational and model data, exploiting the dependence on GMST to estimate how anthropogenic climate change affects the likelihood and severity of extreme events. Rainfall accumulations in Ahr/Erft and the Belgian Meuse catchment vastly exceeded previous observed records. In regions of that limited size the robust estimation of return values and the detection and attribution of rainfall trends are challenging. However, for the larger Western European region it was found that, under current climate conditions, on average one rainfall event of this magnitude can be expected every 400 years at any given location. Consequently, within the entire region, events of similar magnitude are expected to occur more frequently than once in 400 years. Anthropogenic climate change has already increased the intensity of the maximum 1-day rainfall event in the summer season by 3–19 %. The likelihood of such an event to occur today compared to a 1.2 $$^{° }$$ ∘ C cooler climate has increased by a factor of 1.2–9. Models indicate that intensity and frequency of such events will further increase with future global warming. While attribution of small-scale events remains challenging, this study shows that there is a robust increase in the likelihood and severity of rainfall events such as the ones causing extreme impacts in July 2021 when considering a larger region.

Mini-PBPK-Based Population Model and Covariate Analysis to Assess the Complex Pharmacokinetics and Pharmacodynamics of RO7449135, an Anti-KLK5/KLK7 Bispecific Antibody in Cynomolgus Monkeys - Hao Cai; Xun Tao; Jeongsup Shim; Rebecca N. Bauer; Meire Bremer; Wei Bu; Jason LaMar; Rachel Basile; Edward Dere; Tien Nguyen; Steven Laing; Pamela Chan; et al. (The AAPS Journal, 2023)

Determining meteorologically-favorable zones for seasonal influenza activity in Hong Kong - Ka Chun Chong; Paul K. S. Chan; Tsz Cheung Lee; Steven Y. F. Lau; Peng Wu; Christopher K. C. Lai; Kitty S. C. Fung; Cindy W. S. Tse; Shuk Yu Leung; Ka Li Kwok; Conglu Li; Xiaoting Jiang; et al. (International Journal of Biometeorology, 2023)

Toxicological effects of fresh and aged gasoline exhaust particles in Hong Kong - Yik-Sze Lau; Hon-Yin Poon; Bruce Organ; Hsiao-Chi Chuang; Man-Nin Chan; Hai Guo; Steven Sai Hang Ho; Kin-Fai Ho (Journal of Hazardous Materials, 2023)

Plant-mediated synthesis of silver-doped ZnO nanoparticles with high sonocatalytic activity: Sonocatalytic behavior, kinetic and thermodynamic study - Yin Yin Chan; Yean Ling Pang; Steven Lim; Woon Chan Chong; Siew Hoong Shuit (Environmental Science and Pollution Research, 2022)

A prospective cohort study of the psychological consequences of the COVID-19 pandemic on frontline healthcare workers in New York City - Lauren A. Peccoralo; Robert H. Pietrzak; Jordyn H. Feingold; Shumayl Syed; Chi C. Chan; James W. Murrough; Carly Kaplan; Jaclyn Verity; Adriana Feder; Dennis S. Charney; Steven M. Southwick; Jonathan A. Ripp (International Archives of Occupational and Environmental Health, 2022)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

A Scientific Synthesis of Marine Protected Areas in the United States: Status and Recommendations - Jenna Sullivan-Stack; Octavio Aburto-Oropeza; Cassandra M. Brooks; Reniel B. Cabral; Jennifer E. Caselle; Francis Chan; J. Emmett Duffy; Daniel C. Dunn; Alan M. Friedlander; Heather K. Fulton-Bennett; Steven D. Gaines; Leah R. Gerber; et al. (Frontiers in Marine Science, 2022)
Marine protected areas (MPAs) are a key tool for achieving goals for biodiversity conservation and human well-being, including improving climate resilience and equitable access to nature. At a national level, they are central components in the U.S. commitment to conserve at least 30% of U.S. waters by 2030. By definition, the primary goal of an MPA is the long-term conservation of nature; however, not all MPAs provide the same ecological and social benefits. A U.S. system of MPAs that is equitable, well-managed, representative and connected, and includes areas at a level of protection that can deliver desired outcomes is best positioned to support national goals. We used a new MPA framework, The MPA Guide, to assess the level of protection and stage of establishment of the 50 largest U.S. MPAs, which make up 99.7% of the total U.S. MPA area (3.19 million km 2 ). Over 96% of this area, including 99% of that which is fully or highly protected against extractive or destructive human activities, is in the central Pacific ocean. Total MPA area in other regions is sparse – only 1.9% of the U.S. ocean excluding the central Pacific is protected in any kind of MPA (120,976 km 2 ). Over three quarters of the non-central Pacific MPA area is lightly or minimally protected against extractive or destructive human activities. These results highlight an urgent need to improve the quality, quantity, and representativeness of MPA protection in U.S. waters to bring benefits to human and marine communities. We identify and review the state of the science, including focal areas for achieving desired MPA outcomes and lessons learned from places where sound ecological and social design principles come together in MPAs that are set up to achieve national goals for equity, climate resilience, and biodiversity conservation. We recommend key opportunities for action specific to the U.S. context, including increasing funding, research, equity, and protection level for new and existing U.S. MPAs.

Strong Predictive Algorithm of Pathogenesis-Based Biomarkers Improves Parkinson’s Disease Diagnosis - Daniel Kam Yin Chan; Nady Braidy; Ren Fen Chen; Ying Hua Xu; Steven Bentley; Michal Lubomski; Ryan L. Davis; Jack Chen; Carolyn M. Sue; George D. Mellick (Molecular Neurobiology, 2022)

Differences in representation of extreme precipitation events in two high resolution models - Emma D. Thomassen; Elizabeth J. Kendon; Hjalte J. D. Sørup; Steven C. Chan; Peter L. Langen; Ole B. Christensen; Karsten Arnbjerg-Nielsen (Climate Dynamics, 2021)

Proteome Response of Meretrix Bivalves Hepatopancreas Exposed to Paralytic Shellfish Toxins Producing Dinoflagellate Gymnodinium catenatum - Kin-Ka Chan; Nora Fung-Yee Tam; Christie Ng; Celia Sze-Nga Kwok; Steven Jing-Liang Xu; Eric Tung-Po Sze; Fred Wang-Fat Lee (Journal of Marine Science and Engineering, 2021)
Paralytic shellfish toxins (PSTs) contamination of seafood has become a growing global problem. However, the molecular response of bivalves, some of the most popular seafoods, to PSP toxins has seldom been reported and the underlying molecular mechanisms of the interactions between Meretrix meretrix bivalves and PSTs-producing dinoflagellates are scarcely known. This study compared the protein expression profiles between PSP toxin-contaminated and non-PSP toxin contaminated M. meretrix, determined proteome responses and identified potential biomarkers based on feeding experiments. Results showed that the content of total PSP toxins in contaminated bivalves was 40.63 ± 4.08 μg saxitoxin (STX) equivalents per gram, with 95.3% in hepatopancreas, followed by gill (1.82%) and foot (1.79%). According to two-dimensional gel electrophoresis (2-DE), 15 differentially expressed proteins (at least 2-fold difference) between the hepatopancreas of bivalves with and without PSP toxins were detected. Eight of them were successfully identified by MALDI-TOF MS. These were catalase, protein ultraspiracle homolog, G2 and S phase-expression protein, paramyosin, Mn-superoxide dismutase, response regulator receiver domain-containing protein, sarcoplasmic calcium-binding protein and major facilitator superfamily transporters. The differences in the expression levels of the last three proteins involving in cell signaling, structure and membrane transport were 4.2, 5.3 and 4.9-fold, respectively. These proteins could be further developed as potential biomarkers. The other two up-regulated proteins, Mn-superoxide dismutase and catalase, were involved in cell defence mechanisms against oxidative stress, suggesting PSP toxin acts as xenobiotics and poses oxidative stress in bivalves. This study gives insights into the response of bivalves to PSP toxin-producing dinoflagellate at the proteomic level and the potential of using 2-DE to develop specific protein markers in bivalves.

Using a tier classification system to evaluate the quality of bycatch estimates from fisheries - Lee R. Benaka; Andrea N. Chan; Steven J. Kennelly; Noelle A. Olsen (Reviews in Fish Biology and Fisheries, 2021)
Bycatch continues to be a challenge to sustainable fisheries management (The term “bycatch” in this paper covers discards and does not include retained incidental catch). Bycatch estimates can inform stock status determinations by improving understanding of fishing mortality, and help managers monitor the effectiveness of regulations. Assessments of the quality of bycatch estimation programs and procedures are necessary to evaluate the precision and limitations of their results over time. NOAA Fisheries experts used a “Tier Classification System” (TCS) to compare the quality of fish bycatch data and estimation methods for U.S. commercial fisheries in 2005 and 2015. The TCS included criteria related to data adequacy and analytical approaches. A comparison of U.S. fishery tier scores demonstrated that most fisheries were classified into higher tiers in 2015 compared to 2005 due to factors including improved sampling design. In addition, this comparison identified region-specific trends (e.g., mostly improvements occurred for Alaska fisheries with more mixed results for Greater Atlantic fisheries). The improvements in bycatch data quality and estimation methods in the United States are a result of financial investments in observer programs by NOAA Fisheries and industry partners, as well as effective conservation measures implemented by regional fishery management councils and NOAA Fisheries. The TCS was also used to assess bycatch data and estimation methods in all of Australia’s fishery jurisdictions for the decade 2010–19, illustrating the international applicability of the method. Overall, Australian state fisheries scored lower than federally managed fisheries in both the United States and Australia, reflecting the fact that the latter fisheries tend to be larger (and more valuable) than those in state jurisdictions, with a larger investment in observer programs. A comparison of tier scores and estimates of discards by fishery may provide a useful input for decision-making processes regarding allocation of resources to improve bycatch monitoring.

The first multi-model ensemble of regional climate simulations at kilometer-scale resolution, part I: evaluation of precipitation - Nikolina Ban; Cécile Caillaud; Erika Coppola; Emanuela Pichelli; Stefan Sobolowski; Marianna Adinolfi; Bodo Ahrens; Antoinette Alias; Ivonne Anders; Sophie Bastin; Danijel Belušić; Ségolène Berthou; et al. (Climate Dynamics, 2021)
Here we present the first multi-model ensemble of regional climate simulations at kilometer-scale horizontal grid spacing over a decade long period. A total of 23 simulations run with a horizontal grid spacing of $$\sim $$ ∼ 3 km, driven by ERA-Interim reanalysis, and performed by 22 European research groups are analysed. Six different regional climate models (RCMs) are represented in the ensemble. The simulations are compared against available high-resolution precipitation observations and coarse resolution ( $$\sim $$ ∼ 12 km) RCMs with parameterized convection. The model simulations and observations are compared with respect to mean precipitation, precipitation intensity and frequency, and heavy precipitation on daily and hourly timescales in different seasons. The results show that kilometer-scale models produce a more realistic representation of precipitation than the coarse resolution RCMs. The most significant improvements are found for heavy precipitation and precipitation frequency on both daily and hourly time scales in the summer season. In general, kilometer-scale models tend to produce more intense precipitation and reduced wet-hour frequency compared to coarse resolution models. On average, the multi-model mean shows a reduction of bias from $$\sim \,$$ ∼ −40% at 12 km to $$\sim \,$$ ∼ −3% at 3 km for heavy hourly precipitation in summer. Furthermore, the uncertainty ranges i.e. the variability between the models for wet hour frequency is reduced by half with the use of kilometer-scale models. Although differences between the model simulations at the kilometer-scale and observations still exist, it is evident that these simulations are superior to the coarse-resolution RCM simulations in the representing precipitation in the present-day climate, and thus offer a promising way forward for investigations of climate and climate change at local to regional scales.

Enhanced photocatalytic degradation of methyl orange by coconut shell–derived biochar composites under visible LED light irradiation - Yean Ling Pang; Zhi Xuan Law; Steven Lim; Yin Yin Chan; Siew Hoong Shuit; Woon Chan Chong; Chin Wei Lai (Environmental Science and Pollution Research, 2021)

The first multi-model ensemble of regional climate simulations at kilometer-scale resolution part 2: historical and future simulations of precipitation - Emanuela Pichelli; Erika Coppola; Stefan Sobolowski; Nikolina Ban; Filippo Giorgi; Paolo Stocchi; Antoinette Alias; Danijel Belušić; Segolene Berthou; Cecile Caillaud; Rita M. Cardoso; Steven Chan; et al. (Climate Dynamics, 2021)

Biosynthesized Fe- and Ag-doped ZnO nanoparticles using aqueous extract of Clitoria ternatea Linn for enhancement of sonocatalytic degradation of Congo red - Yin Yin Chan; Yean Ling Pang; Steven Lim; Chin Wei Lai; Ahmad Zuhairi Abdullah; Woon Chan Chong (Environmental Science and Pollution Research, 2020)

Europe-wide precipitation projections at convection permitting scale with the Unified Model - Steven C. Chan; Elizabeth J. Kendon; Ségolène Berthou; Giorgia Fosser; Elizabeth Lewis; Hayley J. Fowler (Climate Dynamics, 2020)
For the first time, we analyze 2.2 km UK Met Office Unified Model convection-permitting model (CPM) projections for a pan-European domain. These new simulations represent a major increase in domain size, allowing us to examine the benefits of CPMs across a range of European climates. We find a change to the seasonality of extreme precipitation with warming. In particular, there is a relatively muted response for summer, which contrasts with much larger increases in autumn and winter. This flattens the hourly extreme precipitation seasonal cycle across Northern Europe which has a summer peak in the present climate. Over the Western Mediterranean, where autumn is the main extreme precipitation season, there is a regional increase in hourly extreme precipitation frequency, but local changes for lower precipitation thresholds are often insignificant. For mean precipitation, decreases are projected across Europe in summer, smaller decreases in autumn, and increases in winter; comparable changes are seen in the driving general circulation model (GCM) simulations. The winter mean increase is accompanied by a large decrease of winter mean snowfall. Comparing the driving GCM projections with the CPM ones, the CPMs show a robust enhanced intensification of precipitation extremes at the convection-permitting scale compared to coarser resolution climate model projections across various European regions for summer and autumn.

Pan-European climate at convection-permitting scale: a model intercomparison study - Ségolène Berthou; Elizabeth J. Kendon; Steven C. Chan; Nikolina Ban; David Leutwyler; Christoph Schär; Giorgia Fosser (Climate Dynamics, 2020)

Optimal configuration and resolution for the first convection‐permitting ensemble of climate projections over the United Kingdom - Giorgia Fosser; Elizabeth Kendon; Steven Chan; Adrian Lock; Nigel Roberts; Mike Bush (International Journal of Climatology, 2020)
Convection‐permitting models (CPMs) provide a better representation of sub‐daily precipitation statistics and convective processes on both climate and weather forecasting timescales. This study aims to establish what horizontal resolution and physical process settings are suitable for the first ensemble of convection‐permitting climate projections for the United Kingdom. For this purpose, 12‐year‐long simulations were run using three different convection‐permitting resolutions (grid spacing of 4 km, 2.2 km and 1.5 km) each with several configurations. The focus is on the ability to represent sub‐daily precipitation due to its potential for high impacts on society through flooding. The analysis shows that the use of a finer grid spacing within the convection‐permitting regime improves the representation of sub‐daily precipitation but the added value decreases as the grid becomes increasingly finer, while the computational costs substantially increase. Changes in the representation of physical processes can have as much impact as the grid spacing and can lead to similar differences in the diurnal cycle as between convection‐parametrized models and CPMs. Although the 4km model shows some key deficiencies that make it unreliable for climate projection, the 2.2km model performs as well as the 1.5km model for most of the metrics examined with considerable benefits in terms of computer cost. The optimal configuration and resolution identified here is being used for an ensemble of simulations run within the UK Climate Projections 2018 (UKCP18) project, which allows, for the first time, an estimate of uncertainty in future changes at convection‐permitting scale and providing more reliable climate change projections at local and hourly scales.

Global distribution of the intensity and frequency of hourly precipitation and their responses to ENSO - Xiao-Feng Li; Stephen Blenkinsop; Renaud Barbero; Jingjing Yu; Elizabeth Lewis; Geert Lenderink; Selma Guerreiro; Steven Chan; Yafei Li; Haider Ali; Roberto Villalobos Herrera; Elizabeth Kendon; et al. (Climate Dynamics, 2020)
We investigate the global distribution of hourly precipitation and its connections with the El Niño–Southern Oscillation (ENSO) using both satellite precipitation estimates and the global sub-daily rainfall gauge dataset. Despite limited moisture availability over continental surfaces, we find that the highest mean and extreme hourly precipitation intensity (HPI) values are mainly located over continents rather than over oceans, a feature that is not evident in daily or coarser resolution data. After decomposing the total precipitation into the product of the number of wet hours (NWH) and HPI, we find that ENSO modulates total precipitation mainly through the NWH, while its effects on HPI are more limited. The contrasting responses to ENSO in NWH and HPI is particularly apparent at the rising branches of the Pacific and Atlantic Walker Circulations, and is also notable over land-based gauges in Australia, Malaysia, the USA, Japan and Europe across the whole distribution of hourly precipitation (i.e. extreme, moderate and light precipitation). These results provide new insights into the global precipitation distribution and its response to ENSO forcing.

Investigation of Growth, Lipid Productivity, and Fatty Acid Profiles in Marine Bloom-Forming Dinoflagellates as Potential Feedstock for Biodiesel - Steven Jingliang Xu; Kam-Chau Wu; Sophie Cheuk-Yan Chan; Yiu-Hung Yau; Kin-Ka Chan; Fred Wang-Fat Lee (Journal of Marine Science and Engineering, 2020)
Microalgae-based biodiesel is increasingly recognized as an alternative to crop-based biodiesel. In this study, 10 local strains of dinoflagellates collected from Hong Kong waters, including a monoculture and field sample of Scrippsiella sp. isolated from an algal bloom, were evaluated against the performance of green alga Tetraselmis suecica. The specific growth rate, biomass production, lipid productivity, and fatty acid profile were investigated. The total lipid content of isolated strains ranged from 16.2% to 32.2% of the total dry biomass, whereas palmitic acid (C16:0) and docosahexaenoic acid (DHA, C22:6n3) were dominant in the fatty acid profile. Scrippsiella sp. has a high lipid productivity (47.3 mg/L/day) and fatty acid methyl esters (FAME) content (55.2–73 mg/g dry weight (dw)), which were comparable to that in green alga T. suecica. Further, monoculture and field sampled blooming Scrippsiella sp. showed no significant difference in most parameters, suggesting the possibility of harvesting a natural algal bloom population as a mitigation strategy to harmful algal bloom and to use as biodiesel feedstock. Overall, dinoflagellate species showed a slower growth rate (0.04–0.57 day−1) than most compared species (0.07–1.34 day−1), likely due to a large genome size and low chlorophyll to carbon ratio. Notably, most investigated dinoflagellates were not ideal for mass biodiesel production due to the low growth rate and lipid productivity. However, a high level of polyunsaturated fatty acids (PUFA) in dinoflagellates are prospective for further studies in other biotechnological applications. Though effectively harvesting algal blooming biomass can be complex, it can be further explored as a strategy for algal bloom mitigation and potentially creating values at the advantage of natural bloom when applying harvested biomass for biodiesel and bioactive compounds extraction.

Effect of Roughness on the Dispersion of Dry Powders for Inhalation: a Dynamic Visualization Perspective - Xiang Kou; Paul W. S. Heng; Lai Wah Chan; Steven T. Wereley; M. Teresa Carvajal (AAPS PharmSciTech, 2019)

Connecting Science to Policymakers, Managers, and Citizens - Jane Lubchenco; Bruce Menge; John Barth; Mark Carr; Jennifer Caselle; Francis Chan; Heather Fulton-Bennett; Steven Gaines; Kristy Kroeker; Kristen Milligan; Steven Palumbi; J. Wilson White (Oceanography, 2019)

PISCO: Advances Made Through the Formation of a Large-Scale, Long-Term Consortium for Integrated Understanding of Coastal Ecosystem Dynamics - Bruce Menge; Kristen Milligan; Jennifer Caselle; John Barth; Carol Blanchette; Mark Carr; Francis Chan; Robert Cowen; Mark Denny; Steven Gaines; Gretchen Hofmann; Kristy Kroeker; et al. (Oceanography, 2019)

Correction to: Genetic variant predictors of gene expression provide new insight into risk of colorectal cancer - Stephanie A. Bien; Yu-Ru Su; David V. Conti; Tabitha A. Harrison; Conghui Qu; Xingyi Guo; Yingchang Lu; Demetrius Albanes; Paul L. Auer; Barbara L. Banbury; Sonja I. Berndt; Stéphane Bézieau; et al. (Human Genetics, 2019)

Genetic variant predictors of gene expression provide new insight into risk of colorectal cancer - Stephanie A. Bien; Yu-Ru Su; David V. Conti; Tabitha A. Harrison; Conghui Qu; Xingyi Guo; Yingchang Lu; Demetrius Albanes; Paul L. Auer; Barbara L. Banbury; Sonja I. Berndt; Stéphane Bézieau; et al. (Human Genetics, 2019)

Projected changes in extreme precipitation over Scotland and Northern England using a high-resolution regional climate model - Steven C. Chan; Ron Kahana; Elizabeth J. Kendon; Hayley J. Fowler (Climate Dynamics, 2018)

Impact of Physicochemical Properties of Cellulosic Polymers on Supersaturation Maintenance in Aqueous Drug Solutions - Shiqi Hong; Steven A. Nowak; Chan Lai Wah (AAPS PharmSciTech, 2018)

Quality‐control of an hourly rainfall dataset and climatology of extremes for the UK - Stephen Blenkinsop; Elizabeth Lewis; Steven C. Chan; Hayley J. Fowler (International Journal of Climatology, 2017)
Sub‐daily rainfall extremes may be associated with flash flooding, particularly in urban areas but, compared with extremes on daily timescales, have been relatively little studied in many regions. This paper describes a new, hourly rainfall dataset for the UK based on ∼1600 rain gauges from three different data sources. This includes tipping bucket rain gauge data from the UK Environment Agency (EA), which has been collected for operational purposes, principally flood forecasting. Significant problems in the use of such data for the analysis of extreme events include the recording of accumulated totals, high frequency bucket tips, rain gauge recording errors and the non‐operation of gauges. Given the prospect of an intensification of short‐duration rainfall in a warming climate, the identification of such errors is essential if sub‐daily datasets are to be used to better understand extreme events. We therefore first describe a series of procedures developed to quality control this new dataset. We then analyse ∼380 gauges with near‐complete hourly records for 1992–2011 and map the seasonal climatology of intense rainfall based on UK hourly extremes using annual maxima, n ‐largest events and fixed threshold approaches. We find that the highest frequencies and intensities of hourly extreme rainfall occur during summer when the usual orographically defined pattern of extreme rainfall is replaced by a weaker, north–south pattern. A strong diurnal cycle in hourly extremes, peaking in late afternoon to early evening, is also identified in summer and, for some areas, in spring. This likely reflects the different mechanisms that generate sub‐daily rainfall, with convection dominating during summer. The resulting quality‐controlled hourly rainfall dataset will provide considerable value in several contexts, including the development of standard, globally applicable quality‐control procedures for sub‐daily data, the validation of the new generation of very high‐resolution climate models and improved understanding of the drivers of extreme rainfall.

An update of the WCRF/AICR systematic literature review on esophageal and gastric cancers and citrus fruits intake - Snieguole Vingeliene; Doris S. M. Chan; Dagfinn Aune; Ana R. Vieira; Elli Polemiti; Christophe Stevens; Leila Abar; Deborah Navarro Rosenblatt; Darren C. Greenwood; Teresa Norat (Cancer Causes & Control, 2016)

Use of a robotic device to measure age-related decline in finger proprioception - Morgan L. Ingemanson; Justin B. Rowe; Vicky Chan; Eric T. Wolbrecht; Steven C. Cramer; David J. Reinkensmeyer (Experimental Brain Research, 2016)

A genome-wide association study for colorectal cancer identifies a risk locus in 14q23.1 - Mathieu Lemire; Conghui Qu; Lenora W. M. Loo; Syed H. E. Zaidi; Hansong Wang; Sonja I. Berndt; Stéphane Bézieau; Hermann Brenner; Peter T. Campbell; Andrew T. Chan; Jenny Chang-Claude; Mengmeng Du; et al. (Human Genetics, 2015)

Decline in Helicoverpa armigera nucleopolyhedrovirus occlusion body yields with increasing infection cell density in vitro is strongly correlated with viral DNA levels - Hoai T. Huynh; Trinh T. B. Tran; Leslie C. L. Chan; Lars K. Nielsen; Steven Reid (Archives of Virology, 2015)

A herpes simplex virus type 1 mutant disrupted for microRNA H2 with increased neurovirulence and rate of reactivation - Xianzhi Jiang; Don Brown; Nelson Osorio; Chinhui Hsiang; Lily Li; Lucas Chan; Lbachir BenMohamed; Steven L. Wechsler (Journal of NeuroVirology, 2015)

The effect of cell line, phylogenetics and medium on baculovirus budded virus yield and quality - Leila Matindoost; Hao Hu; Leslie C. L. Chan; Lars K. Nielsen; Steven Reid (Archives of Virology, 2014)

Does increasing the spatial resolution of a regional climate model improve the simulated daily precipitation? - Steven C. Chan; Elizabeth J. Kendon; Hayley J. Fowler; Stephen Blenkinsop; Christopher A. T. Ferro; David B. Stephenson (Climate Dynamics, 2013)

Comparative mapping in watermelon [Citrullus lanatus (Thunb.) Matsum. et Nakai] - Katherine Sandlin; Jason Prothro; Adam Heesacker; Nelly Khalilian; Rebecca Okashah; Wenwen Xiang; Eleni Bachlava; David G. Caldwell; Chris A. Taylor; Danelle K. Seymour; Victoria White; Eva Chan; et al. (Theoretical and Applied Genetics, 2012)

A proxy for high-resolution regional reanalysis for the Southeast United States: assessment of precipitation variability in dynamically downscaled reanalyses - Lydia Stefanova; Vasubandhu Misra; Steven Chan; Melissa Griffin; James J. O’Brien; Thomas J. Smith III (Climate Dynamics, 2012)

Meta-analysis of new genome-wide association studies of colorectal cancer risk - Ulrike Peters; Carolyn M. Hutter; Li Hsu; Fredrick R. Schumacher; David V. Conti; Christopher S. Carlson; Christopher K. Edlund; Robert W. Haile; Steven Gallinger; Brent W. Zanke; Mathieu Lemire; Jagadish Rangrej; et al. (Human Genetics, 2012)

Forest Management, Engineering, and Operations / Global Competency and Issues in Contemporary Education - Finto Antony; Lewis Jordan; Laurie Schimleck; Richard Daniels; Rapeepan Kantavichai; Lara Hansen; Jessica Hitt; William Hubbard; Gwendolyn Boyd; Ryan Boyles; Heather Dinon; Joshua Idassi; et al. (Journal of Forestry, 2011)
31Maps depicting spatial variation in wood properties are important for forest product industries as they aid decision making regarding raw material procurement, can assist in product categorization and help improve utilization. Loblolly pine is an important commercial species grown throughout the southern Unites States of America (USA). Wood Quality Consortium (WQC)—a joint collaboration between the University of Georgia, USDA Forest Service and industries—was established in 1999 with the objective of characterizing wood property variation of plantation grown loblolly pine. Data on wood specific gravity (SG), modulus of elasticity (MOE) and modulus of rupture (MOR) collected by the WQC was utilized in this study. Maps showing spatial variation in SG at different stand ages and SG, MOE and MOR at different heights within a tree were developed using appropriate spatial prediction methods (kriging). The geographical variation of these wood properties across southeastern USA was demonstrated here.

Haplotype structure in Ashkenazi Jewish BRCA1 and BRCA2 mutation carriers - Kate M. Im; Tomas Kirchhoff; Xianshu Wang; Todd Green; Clement Y. Chow; Joseph Vijai; Joshua Korn; Mia M. Gaudet; Zachary Fredericksen; V. Shane Pankratz; Candace Guiducci; Andrew Crenshaw; et al. (Human Genetics, 2011)

High-resolution subtropical summer precipitation derived from dynamical downscaling of the NCEP/DOE reanalysis: how much small-scale information is added by a regional model? - Young-Kwon Lim; Lydia B. Stefanova; Steven C. Chan; Siegfried D. Schubert; James J. O’Brien (Climate Dynamics, 2011)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Comparative Phloem Chemistry of Manchurian (Fraxinus mandshurica) and Two North American Ash Species (Fraxinus americana and Fraxinus pennsylvanica) - Alieta Eyles; William Jones; Ken Riedl; Don Cipollini; Steven Schwartz; Kenneth Chan; Daniel A. Herms; Pierluigi Bonello (Journal of Chemical Ecology, 2007)

A mutant deleted for most of the herpes simplex virus type 1 (HSV-1) UOL gene does not affect the spontaneous reactivation phenotype in rabbits - David Chan; Jacob Cohen; Julie Naito; Kevin R Mott; Nelson Osorio; Ling Jin; Nigel W Fraser; Clinton Jones; Steven L Wechsler; Guey Chuen Perng (Journal of NeuroVirology, 2006)

PROPERTIES OF A UNIQUE MUTANT OF HELICOVERPA ARMIGERA SINGLE-NUCLEOCAPSID NUCLEOPOLYHEDROVIRUS THAT EXHIBITS A PARTIAL MANY POLYHEDRA AND FEW POLYHEDRA PHENOTYPE ON EXTENDED SERIAL PASSAGING IN SUSPENSION CELL CULTURES - MÁRCIA R. S. PEDRINI; LARS K. NIELSEN; STEVEN REID; LESLIE C. L. CHAN (In Vitro Cellular & Developmental Biology - Animal, 2005)